2021
DOI: 10.3389/fonc.2021.643872
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Relevance of Claudin 18.2 Expression in Gastric Cancer: A Meta-Analysis

Abstract: An increasing number of tumor markers have been discovered to have potential efficacy as diagnostic and prognostic tools in gastric cancer. We aimed to assess putative correlations between claudin 18.2 expression and pathological or prognosis features in patients with gastric cancer. MEDLINE, Web of Science, EBSCO, and ClinicalTrials.gov were used to search for relevant studies from their inception to 30 October 2020. Finally, a total of six articles were included in this meta-analysis. Review Manager 5 softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
1
28
1
Order By: Relevance
“…15,17,18 However, a meta-analysis did not find any correlation between claudin-18.2 staining and clinicopathologic features. 4 Our data suggested that claudin-18 staining alone may lead to few gastric adenocarcinomas being undetected. A combination of this technique with a review of clinical history as well as staining for other IHC markers may reduce the possibility of misdiagnosis.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…15,17,18 However, a meta-analysis did not find any correlation between claudin-18.2 staining and clinicopathologic features. 4 Our data suggested that claudin-18 staining alone may lead to few gastric adenocarcinomas being undetected. A combination of this technique with a review of clinical history as well as staining for other IHC markers may reduce the possibility of misdiagnosis.…”
Section: Discussionmentioning
confidence: 65%
“…A wide range of expression rates of claudin-18 in gastric cancer, from 12.5% to 77%, were reported in other studies. 4,[16][17][18][19] Similarly, the reported positive rates in esophageal adenocarcinoma varied from 18.4% to 78%. 18,20 The wide ranges may reflect different sensitivity of antibody clones and scoring systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLDN18.2 expression was significantly associated with a diffuse histologic type, non-antral location, and EBV-positivity [41][42][43]. A majority of the studies reported that high expression of CLDN 18.2 was not associated with patient survival [42,[121][122][123][124].…”
Section: Cldn182mentioning
confidence: 98%
“…In previous studies, CLDN18.2 expression in tumor cells was only determined by IHC [124]. Membranous staining of moderate to strong (2+/3+) intensity was regarded as high expression in tumor cells, and the proportion of CLDN18.2+ cells was calculated.…”
Section: Cldn182mentioning
confidence: 99%